P300 amplitudes in the concealed information test are less affected by depth of processing than electrodermal responses - Gamer, Matthias; Berti, Stefan (Frontiers in Human Neuroscience, 2012)
The Concealed Information Test (CIT) has been used in the laboratory as well as in field applications to detect concealed crime related memories. The presentation of crime relevant details to guilty suspects has been shown to elicit enhanced N200 and P300 amplitudes of the event-related brain potentials as well as greater skin conductance responses (SCRs) as compared to neutral test items. These electrophysiological and electrodermal responses were found to incrementally contribute to the validity of the test, thereby suggesting that these response systems are sensitive to different psychological processes. In the current study, we tested whether depth of processing differentially affects N200, P300 and SCR amplitudes in the CIT. Twenty participants carried out a mock crime and became familiar with central and peripheral crime details. A CIT that was conducted one week later revealed that SCR amplitudes were larger for central details although central and peripheral items were remembered equally well in a subsequent explicit memory test. By contrast, P300 amplitudes elicited by crime related details were larger but did not differ significantly between question types. N200 amplitudes did not allow for detecting concealed knowledge in this study. These results indicate that depth of processing might be one factor that differentially affects central and autonomic nervous system responses to concealed information. Such differentiation might be highly relevant for field applications of the CIT.